2007
DOI: 10.1002/pros.20653
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol sensitizes androgen independent prostate cancer cells to death‐receptor mediated apoptosis through multiple mechanisms

Abstract: Altering apoptotic susceptibility in advanced androgen independent disease requires manipulation of a broad signaling pathway. Use of resveratrol or inhibition of Akt phosphorylation may represent an important therapeutic approach in combination with conventional therapies for the treatment of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 54 publications
5
56
2
Order By: Relevance
“…These may have important potential implications, as they directly relate to the unsettled issue of bioavailability of resveratrol as well as provide support to recent reports showing that resveratrol sensitizes cancer cells to other chemotherapeutic agents, which act by binding to cell surface death receptors, for example, TRAIL [31]. Data showing that resveratrol increases its own uptake, as illustrated by our experiments using normal prostate cells, also raise the tantalizing possibility that resveratrol might perturb membrane structure and function in ways that facilitate the targeting of death receptors and, hence, improve responsiveness to chemotherapeutic agents without compromising the likelihood for developing chemoresistance [31][32][33]. It is noteworthy to point out that the present studies also showed considerable binding of [ 3 H]resveratrol to cell extracts of PrSCs and PrECs, even when cells are immediately harvested after labeling with resveratrol, and that there was 1.6-fold labeling in PrECs compared with PrSCs ( Figure 1).…”
Section: Discussionsupporting
confidence: 56%
“…These may have important potential implications, as they directly relate to the unsettled issue of bioavailability of resveratrol as well as provide support to recent reports showing that resveratrol sensitizes cancer cells to other chemotherapeutic agents, which act by binding to cell surface death receptors, for example, TRAIL [31]. Data showing that resveratrol increases its own uptake, as illustrated by our experiments using normal prostate cells, also raise the tantalizing possibility that resveratrol might perturb membrane structure and function in ways that facilitate the targeting of death receptors and, hence, improve responsiveness to chemotherapeutic agents without compromising the likelihood for developing chemoresistance [31][32][33]. It is noteworthy to point out that the present studies also showed considerable binding of [ 3 H]resveratrol to cell extracts of PrSCs and PrECs, even when cells are immediately harvested after labeling with resveratrol, and that there was 1.6-fold labeling in PrECs compared with PrSCs ( Figure 1).…”
Section: Discussionsupporting
confidence: 56%
“…24 To further investigate the biochemical mechanisms involved we next looked at the activation of the caspase cascade and demonstrated that TRAIL induces apoptosis by the activation of Caspases 8, 9 and 7 as previously described. 16 Pre-exposure of the cells to hypoxia significantly prevented the activation of these caspases, which was associated with their resistance to apoptosis. Nagaraj et al has recently demonstrated a similar effect of hypoxia on TRAIL-induced Caspases 3, 8 and 9 activation in oral squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 95%
“…Protein concentration of each sample was determined by the Bradford method and activity was expressed as change in fluorescence/min/ mg of protein. 16 …”
Section: Caspase Activity Assaysmentioning
confidence: 99%
See 2 more Smart Citations